Sumpah Pemuda 1928: Reinterpretasi Perjuangan Pemuda Indonesia di Era Society 5.0 - Bustan; Muhammad Syukur (Universitas Negeri Makassar, 2023)
October 28, 1928 was a historic day for the Indonesian people. How could it not be, this moment marked the birth of a sacred and meaningful pledge from Indonesian youth known as the Youth Pledge. This study is interesting because recently Indonesian people, especially the millennial generation, tend to act individually. This is of course a problem because this nation needs collaborative work to become an advanced nation. This is of course a problem because this nation needs collaborative work to become an advanced nation. This research uses a qualitative approach. The research method is the historical method using four stages, namely, first, heuristics, collecting relevant data through literature reviews, and interviews. The second is criticism, selecting and sorting data according to needs. Third, interpretation, interpreting the selected data by giving meaning. The fourth is historiography, presenting or conveying the synthesis obtained in the form of a historical story. The results of the study illustrate that the pledge uttered by the youths in 1928 showed a knight's spirit. Inflame the spirit of national unity and integrity. Through the youth oath we are taught to respect differences both in ethnicity, culture, regional language and differences in interests to build harmonization within the framework of togetherness. Of course, if we learn from past events, the youth oath can be a lesson to strengthen the solidarity of young people to contribute to this nation.